2021
DOI: 10.1111/nin.12466
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of severe maternal morbidity among Black women

Abstract: Black women are 3–4 times more likely to die from a pregnancy‐related complication and twice as likely to experience severe maternal morbidity when compared to white women in the United States. The risks for pregnancy‐related maternal mortality are well documented, yet Black women's experiences of life‐threatening morbidity are essentially absent in the nursing literature. The purpose of this interpretive phenomenological study was to understand the experiences of Black women who developed severe maternal morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
0
24
2
Order By: Relevance
“…[58][59][60] Racial and ethnic disparities in SMM prevalence are known to persist. 61,62 Even though we did not observe a statistically significant effect modification between heat and race and ethnicity in associations between heat exposure and risk of SMM, we observed a higher magnitude of associations in Hispanic mothers. Prior studies demonstrated that African American women can be disproportionately burdened by SMM risks, followed by Hispanic women and other racial or ethnic minoritized groups.…”
Section: Jama Network Open | Environmental Healthcontrasting
confidence: 86%
See 1 more Smart Citation
“…[58][59][60] Racial and ethnic disparities in SMM prevalence are known to persist. 61,62 Even though we did not observe a statistically significant effect modification between heat and race and ethnicity in associations between heat exposure and risk of SMM, we observed a higher magnitude of associations in Hispanic mothers. Prior studies demonstrated that African American women can be disproportionately burdened by SMM risks, followed by Hispanic women and other racial or ethnic minoritized groups.…”
Section: Jama Network Open | Environmental Healthcontrasting
confidence: 86%
“…To interpret racial and ethnic heterogeneity, researchers have called for considering race as a socially defined construct. 61,66 We observed higher proportions of mothers with a lower education or income level in our cohort for African American and Hispanic populations compared with Asian or non-Hispanic White mothers. Moreover, we found significantly higher associations between heat exposure and risk of SMM among mothers with a lower education level.…”
Section: Jama Network Open | Environmental Healthmentioning
confidence: 60%
“…Black midwives were almost eradicated and those that remained were subject to intense scrutiny and policing by local health departments 15 . The loss of Black midwives as the primary pregnancy and birth attendants for Black communities helped lay the groundwork for the widening gap in racial disparities in maternal mortality rates that persist today 19 . Black midwives were replaced by White physicians and nurse midwives, and this shift was accompanied by a racist obstetric system and the move of birth out of the community and to the hospital.…”
Section: Commentarymentioning
confidence: 99%
“…I wanted to know how race predisposes someone to die from a preventative pregnancy-related condition during childbirth or postpartum. My research into the experience of severe maternal morbidity among Black women led me on a journey to understanding racism (Canty, 2020(Canty, , 2022.…”
mentioning
confidence: 99%
“…When I started my research and reviewed the literature, I found very little nursing research that addressed Black maternal health. I found a few studies examining Black women and their experience in childbirth and nothing on Black women who suffered severe pregnancy‐related complications (Canty, 2020). What I found in this literature search were predominantly epidemiological studies that identified that racial disparities exist, with Black women disproportionately representing severe maternal morbidity compared to other racial and ethnic groups (Aseltine et al, 2015; Gyamfi‐Bannerman et al, 2018; Howland et al, 2019; Leonard et al, 2019; Rosenberg et al, 2006; Tangel et al, 2019).…”
mentioning
confidence: 99%